Response Reduction Factor for Mansory Buildings - Shrestha, Jagat Kumar (Nepal Journal of Science and Technology, 2020)
Most of the seismic codes used today incorporate the nonlinear response of a structure by providing an appropriate response reduction factor so that a linear elastic force-based approach can be used in designs. This study focuses on evaluating the response reduction factor for masonry buildings with different mechanical properties, which are used in modern codes to scale down the elastic response of the structure. Using a similar frame-approach, a nonlinear static pushover analysis is carried out on the analytical models of masonry building in finite element analysis software SAP 2000v 20.0.0. The response reduction factor components, flexibility, and over strength were computed from the results obtained from the nonlinear static pushover analysis. Finally, the response reduction factor is evaluated for different masonry buildings. It is concluded that the R-value given in IS: 1893-2016 for unreinforced masonry is not recommended for random rubble stone masonry buildings in mud mortar.